Community Based Flash Flood Early Warning System: a Low-cost Technology for Nepalese Mountains - Adhikari, Basanta Raj; Sitoula, Nagendra Raj (Bulletin of the Department of Geology, 2018)
Every year, flood impose substantial economic, social and environmental cost on Nepalese community through direct damage to residential, commercial, educational and structures. Moreover, the flood destroys animal farm, commercial stock and records and other content of the building and pollutes the water. Early Warning Systems are important to save such lives and properties which involves computer, satellite data and high accurate operating system but this system is very costly in terms of installation as well as operation and maintenance leading to hindrance in the sustainability of the system. However, high-tech technology is very expensive and not feasible in Nepal and therefore low-cost and easy operating system is needed in the rural parts of Nepal. The system includes Solar panel, Siren, Ultrasonic sensor, processing unit, and battery. The ultrasonic sensor sense water level and the siren will automatically start. The threshold can be set up according to the space and time. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 87-92